A hybrid neuro-fuzzy controller for brushless DC motors - Gokbulut, Muammer; Dandil, Besir; Bal, Cafer (Springer-Verlag Berlin, 2006)
In this paper, a hybrid neuro-fuzzy controller (NFC) is presented for the speed control of brushless DC motors to improve the control performance of the drive under transient and steady state conditions. In the hybrid control system, proportional-derivative (PD) type neuro-fuzzy controller (NFC) is the main tracking controller, and an integral compensator is proposed to compensate the steady state errors. A simple and smooth activation mechanism described for integral compensator modifies the control law adaptively. The presented BLDC drive has fast tracking capability, less steady state error and robust to load disturbance, and do not need complicated control method. Experimental results showing the effectiveness of the proposed control system are presented.
14th Turkish Symposium on Artificial Intelligence and Neural Networks -- JUN 16-17, 2005 -- Izmir, TURKEY
Keywords: Tracking Control; Network; Implementation